Analysis of Bankruptcy Prediction Accuracy Using the Altman Z-Score, Springate, Taffler, and Zmijewski Models in Property & Real Estate Companies Listed on the IDX (2020-2023) - Alvin Matheus Reinhard Marpaung; Irni Yunita (SMARTINDO, 2026)
Purpose – This research assesses bankruptcy predictions derived from various models to identify the most accurate approach, especially for real estate companies that are publicly traded and listed on the Jakarta Stock Exchange between 2020 and 2023. It also seeks to examine the bankruptcy tendencies of each chosen company, as indicated by the respective models. Design/methodology/approach – Evaluating a company's financial stability necessitates a comprehensive analysis employing models such as the Altman, Springate, Taffler, and Zmijewski Z-score to forecast the potential hazards of future insolvency. Originality – This research assesses the bankruptcy prognosis scores of real estate firms by comparing them to actual outcomes, as demonstrated by the net losses incurred between 2020 and 2023. To select the model exhibiting the highest accuracy and the lowest error rates, Type I and Type II error analyses are conducted. Findings and Discussion – Taffler's model predicts real estate company bankruptcy best, followed by Altman Z-Score and Zmijewski, and Springate's least accurately. It recommends that enterprises continuously assess financial performance, refrain from incurring excessive debt, maintain adequate current assets to fulfill liabilities, and improve profit margins. Conclusion – This study recommends that companies perform regular financial assessments, limit reliance on debt to finance assets, maintain sufficient current assets to cover liabilities, and work on improving profit margins.